Effect of Beverages on Color Change of Glazed Monolithic Zirconia Ceramic - Delaram Gheytasi; Ezatollah Jalalian; Mohammadjavad Etesami; Faezeh Amiri; Farzan Younesi (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the effect of beverages on the color change of glazed monolithic zirconia ceramic. Material and Methods: This in vitrostudy evaluated 18 A2-shade disc-shaped monolithic zirconia specimens measuring 10 x 2 mm. All specimens were sintered, coated with a thin layer of glaze paste, heated in a vacuum furnace, and were subjected to 5000 thermal cycles at 5 and 55 °C. The specimens were then randomized into three groups (n=6) for immersion in orange juice, tea, and distilled water for 135 minutes/day for 24 days and incubated. The color of specimens was measured before and after immersion by a spectrophotometer, and the color change (∆E) was calculated according to the CIE L*a*b* color space. Data were analyzed using one-way ANOVA and Tukey's post-hoc test (alpha=0.05). Results: All three groups experienced a color change after immersion (p<0.05). The ∆E was maximum in tea (2.05±1.04) and minimum in orange juice (0.81±0.57). Significant differences were noted between orange juice and tea (p<0.001), and distilled water and tea (p<0.001) in ∆L, and orange juice and tea (p=0.023), and distilled water and tea (p=0.030) in ∆E. Conclusion: The results indicated that tea caused maximum color change and maximum reduction in lightness (L*) in glazed monolithic zirconia ceramic; however, the color change was within the clinically acceptable range (∆E<3.7).